2014
DOI: 10.3791/51475
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Profiling of the Invasive Tumor Microenvironment in a 3-Dimensional Model of Colorectal Cancer Cells and <em>Ex vivo</em> Fibroblasts

Abstract: Invading colorectal cancer (CRC) cells have acquired the capacity to break free from their sister cells, infiltrate the stroma, and remodel the extracellular matrix (ECM). Characterizing the biology of this phenotypically distinct group of cells could substantially improve our understanding of early events during the metastatic cascade.Tumor invasion is a dynamic process facilitated by bidirectional interactions between malignant epithelium and the cancer associated stroma. In order to examine cell-specific re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
(14 reference statements)
0
2
0
Order By: Relevance
“…The remodeling process includes the degradation of preexisting ECM molecules by proteolytic enzymes and the neosynthesis of ECM secreted by tumor cells and/or stromal cells [29][30][31]. As previous studies have suggested that FN could be produced by various types of cells including tumor cells [32], we identified a positive association between stromal FN expression and the levels of FN expressed in GBC epithelial cells.…”
Section: Discussionmentioning
confidence: 62%
“…The remodeling process includes the degradation of preexisting ECM molecules by proteolytic enzymes and the neosynthesis of ECM secreted by tumor cells and/or stromal cells [29][30][31]. As previous studies have suggested that FN could be produced by various types of cells including tumor cells [32], we identified a positive association between stromal FN expression and the levels of FN expressed in GBC epithelial cells.…”
Section: Discussionmentioning
confidence: 62%
“…Also, in our protocol organotypic slices were incubated in ethanol and it has been reported that ethanol conserves tissue morphology and RNA integrity [ 66 ]. Other protocols of LMD on organotypic slices imply performing a supplemental cut of the organotypic slices with a cryostat to obtain 10–20μm thick slices [ 67 , 68 ], while in this study mRNA expression was analysed directly after the LMD of 300–400μm thick tissue. Thus, this protocol allows having easily reproducible results.…”
Section: Discussionmentioning
confidence: 99%